Simulasi Perbaikan Sistem Antrian untuk Mengurangi Waktu Tunggu Pasien Poli Umum di Klinik XYZ Menggunakan ProModel - Andre Sugioko; Cecilia Angelina; Trifenaus Prabu Hidayat (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2025)
The long patient waiting time in general outpatient services has become a major problem at Clinic XYZ, particularly during the screening stage and doctor consultations at peak hours. This condition negatively affects patient satisfaction and service effectiveness. This study aims to identify the causes of prolonged waiting times, propose alternative improvements, and evaluate the effectiveness of solutions through simulation using ProModel software. The simulation model was developed to represent real conditions and test several improvement scenarios. The results show that nearly 50% of patients’ time in the system is spent waiting. Four improvement proposals were suggested, namely adding more doctors, redistributing nurses’ tasks, increasing screening capacity, and implementing a single-queue system. The best proposal, which applies consistently to both morning and afternoon sessions, is the addition of doctors. Based on the analysis, this solution proved to be the most effective, reducing total waiting time by 39.75% in the morning scenario and 33.74% in the afternoon scenario. This recommendation provides a strategic basis for improving service efficiency and patient satisfaction at Clinic XYZ.